THE DYNAMICS OF DELTAMETHRIN IN SOILS FROM YOGYAKARTA SPECIAL TERRITORY - , Syukria Kurniawati ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Deltamethrin is a synthetic pyrethroid and one of the most widely used insecticide for crop protection. Intensive use of deltamethrin on the agricultural land will cause potential accumulation and appearance of residues in crops and soil environment. Increasing deltamethrin residues in the long term will disrupt the ecosystem balance and cause environmental problems. Therefore, the dynamics and behavior of deltamethrin in soil environments should be investigated to evaluate the level of safety and effectiveness of insecticide deltamethrin in agricultural activities. Laboratory trials were conducted to investigate the dynamics of the insecticide in soils obtained from three different areas in Yogyakarta Special Territory: Pakem, Wonolelo and Glagah, including the sorption, the retention, the mobility, and the dissipation. Batch experiments were carried out in the sorption study whereas soil column were used to study the retention and mobility of deltamethrin in soils. DT50 determinations were carried out by placing 500 mg soils which were deltamethrin has been applied on media covered with alumunium foil. The soils were sun exposed for 30 days. Soil samples for deltamethrin analysis were collected after 0, 1, 2, 3, 5, 7, 10, 20 and 30 days of application. Sorption isotherm of deltamethrin follows the Freundlich adsorption model (r 2 =0.999).The stronger deltamethrin sorption were observed for soils with higher content of organic matter. In soil column studies (30 cm soil depth), cumulative leaching was generally low, and deltamethrin were detected at 5-10 cm depth in soils within 2, 5 and 10 days. Microbial activitiy appeared to dominate the dissipation process in the dark conditions whereas under the sunexposure conditions, several factors affect the dissipation including microbial activity, volatilization and photolysis.